2015
DOI: 10.1186/s12894-015-0058-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical intervals and diagnostic characteristics in a cohort of prostate cancer patients in Spain: a multicentre observational study

Abstract: BackgroundLittle is known about the healthcare process for patients with prostate cancer, mainly because hospital-based data are not routinely published. The main objective of this study was to determine the clinical characteristics of prostate cancer patients, the, diagnostic process and the factors that might influence intervals from consultation to diagnosis and from diagnosis to treatment.MethodsWe conducted a multicentre, cohort study in seven hospitals in Spain. Patients’ characteristics and diagnostic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
4
0
2
Order By: Relevance
“…We performed a multicenter, cohort study of bladder and prostate cancer, in Spain [ 11 ]. The research ethics committee from each of the seven tertiary participating hospitals (Additional file 1 ) approved the protocol.…”
Section: Main Textmentioning
confidence: 99%
“…We performed a multicenter, cohort study of bladder and prostate cancer, in Spain [ 11 ]. The research ethics committee from each of the seven tertiary participating hospitals (Additional file 1 ) approved the protocol.…”
Section: Main Textmentioning
confidence: 99%
“…In Canada 9 , a research revealed that from the diagnosis to the start of radiotherapy, intermediate-and high-risk men had a shorter waiting time when compared to those at low risk. As in Spain 20 , men with high PSA and high Gleason score obtained a lower interval between diagnosis and treatment.…”
Section: Variables Time Between First Consultation and Onset Of Treatmentioning
confidence: 85%
“…In the two US studies cited above 12,13 , both found that black men were younger, had lower income and with a lower educational level when compared to whites. However, a Spanish study 20 did not find an association between the time elapsed from the diagnosis to the first treatment with the educational level. Although inequalities by schooling level in the use of health services are decreasing consistently in Brazil 19 , it is still a huge challenge.…”
Section: Variables Time Between First Consultation and Onset Of Treatmentioning
confidence: 86%
“…En el cáncer de próstata ocurre también que muchos pacientes tienen síntomas urinarios de larga evolución por hipertrofia benigna y resulta difícil determinar en qué momento atribuirlos al cáncer. Esto coincide con trabajos anteriores 9 , 25 .…”
Section: Discussionunclassified
“…En el realizado por el grupo ICBP en 2018, las medianas para el CCR oscilaron entre 27 y 76 días 19 y para el pulmón entre 25 y 45 18 . En el estudio de Bonfill et al, el tiempo invertido en el diagnóstico desde la consulta de urología tiene una mediana de 89 días en próstata 25 y 104 en vejiga 30 .…”
Section: Discussionunclassified